Differentiating benign from malignant vertebral fractures using T1‐weighted dynamic contrast‐enhanced MRI. Issue 4 (5th February 2015) - Arevalo‐Perez, Julio; Peck, Kyung K.; Lyo, John K.; Holodny, Andrei I.; Lis, Eric; Karimi, Sasan
<x xml:space="preserve">Abstract</x> Purpose To differentiate pathologic from benign vertebral fractures, which can be challenging. We hypothesized that dynamic contrast‐enhanced magnetic resonance imaging (DCE‐MRI) can aid in the noninvasive distinction between pathologic and benign fractures. Materials and Methods Consecutive patients with vertebral fractures who underwent DCE‐MRI, biopsy, and kyphoplasty were reviewed. Forty‐seven fractures were separated into pathologic and benign fractures. Benign fractures were in turn separated into acute and chronic fractures for further comparison. Regions of interest (ROIs) were placed over fractured vertebral bodies. Perfusion parameters: plasma volume (Vp), Ktrans, wash‐in slope, peak enhancement, and area under the curve (AUC) were measured and compared between the three different groups of fractures. A Mann–Whitney U‐test was conducted to assess the difference between the groups. Results Pathologic fractures had significantly higher (P < 0.01) perfusion parameters (Vp, Ktrans, wash‐in slope, peak enhancement, and AUC) compared with benign fractures. We also found significant differences (P < 0.001) in all parameters between chronic and acute fractures. Vp and Ktrans were able to differentiate between pathologic and acute fractures (P < 0.01). No significant differences were found with peak enhancement (P = 0.21) and AUC (P = 0.4) between pathologic and acute fractures. Conclusion Our data demonstrate that T1‐weighted DCE‐MRI has potential to differentiate between pathologic vs. benign, acute vs. chronic, and most important, benign acute vs. pathologic vertebral fractures. J. Magn. Reson. Imaging 2015;42:1039–1047.